Female entrepreneurship : a research agenda - Henry, Colette; McGowan, Pauric (International journal of entrepreneurial behaviour & research ;, 2005)
In recent years, the promotion of female entrepreneurship has become a key area of debate among academics, policy makers and support agencies. This e-book on female entrepreneurship represents a significant contribution to the field, and is the first edited collection of articles which seriously address the challenges that women face in new venturing and enterprise development.